Taxation in insolvency (bankruptcy) procedures of legal entities - I. A. Tsindeliani; T. D. Sadovskaya; E. G. Vasilyeva; Zh. G. Popkova (Правоприменение, 2024)
Subject. The article analyzes a set of norms related to the legal regulation of personal income tax, corporate income tax, VAT, and other taxes, as well as the order of their collection (payment) from a bankrupt, depending on its organizational and legal form. The choice of the research object is due to the presence of problems related to ambiguous issues in taxation in bankruptcy proceedings.The purpose of the study. The article attempts to comprehensively analyze the legal support of the current measures regulating the taxation of bankrupt organizations and individuals, current law enforcement practice, and the legal positions of the country's highest courts.Methodology. The leading research method is a formal legal one.Conclusions. The article reveals and concretizes a number of legal problems. The authors argue their own point of view on the taxation of bankrupt organizations and individuals, taking into account the practice of the highest judicial authorities, which, according to the authors.It is concluded that there are grounds to talk about the formation of such a new legal institution of financial law as "public bankruptcy law".